The Effectiveness of Experience, Generalization, Reinforcement Application (EGRA) Technique toward Students’ Vocabulary Achievement: A Study at SMPN 1 Batang Anai - Jaya, Harfitri Ulfa; Safitri, Dian (Journal of English Language Teaching, 2024)
This study aimed to evaluate the effectiveness of the EGRA learning model in improving the vocabulary. The research followed a quasi-experimental design, specifically a two-group pretest-posttest design. The population of the study consisted of 62 students from seventh classes of SMP 2 Batang Anai. A sampling method was used to select a sample of 32 students from class 7.1 as the experimental group and another 30 students from class 7.2 as the control group. The results indicated that the EGRA learning model was effective in enhancing the Vocabulary skill in class 7.1 as experimental class. The findings of this study provide evidence that the EGRA learning model can be beneficial in teaching vocabulary skills in foreign languages.